Predicting COVID-19 community infection relative risk with a Dynamic Bayesian Network - Johnson, Daniel P.; Lulla, Vijay (Frontiers in Public Health, 2022)
As COVID-19 continues to impact the United States and the world at large it is becoming increasingly necessary to develop methods which predict local scale spread of the disease. This is especially important as newer variants of the virus are likely to emerge and threaten community spread. We develop a Dynamic Bayesian Network (DBN) to predict community-level relative risk of COVID-19 infection at the census tract scale in the U.S. state of Indiana. The model incorporates measures of social and environmental vulnerability – including environmental determinants of COVID-19 infection – into a spatial temporal prediction of infection relative risk 1-month into the future. The DBN significantly outperforms five other modelling techniques used for comparison and which are typically applied in spatial epidemiological applications. The logic behind the DBN also makes it very well suited for spatial – temporal prediction and for “what-if” analysis. The research results also highlight the need for further research using DBN-type approaches that incorporate methods of artificial intelligence into modelling dynamic processes, especially prominent within spatial epidemiologic applications.